2022
DOI: 10.3390/su14148701
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Level and Consumption Behavior of Native Plants, Meats, and Drinking Waters with High Fluoride Concentrations about the Relation to the Potential Health Risk of Fluoride in Lamphun Province Thailand: A Case Study

Abstract: Fluoride exposure from natural, agricultural, and industrial sources has harmed people living in fluoride-affected areas. Fluoride accumulates in the human body after being exposed to it through the food chain. The population consisted of 371 community health volunteers who were surveyed and chosen based on personal fluoride information. Only 39 residents were chosen to be interviewed and take part in the trial, which involved drinking fluoride-containing groundwater (>1.5 part per million: ppm) and urine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The primary route of human exposure to fluoride is through food and water, which causes health implications in fluoride-contaminated areas. For example, Tewarangsri et al [ 6 ] found that the risks to health in fluoride-contaminated areas are elevated. The HRA in fluoride-contaminated locations when bottled water was consumed was greater than 1 (hazard quotient: HQ > 1), corresponding with other areas where fluoride-containing streams were traversed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary route of human exposure to fluoride is through food and water, which causes health implications in fluoride-contaminated areas. For example, Tewarangsri et al [ 6 ] found that the risks to health in fluoride-contaminated areas are elevated. The HRA in fluoride-contaminated locations when bottled water was consumed was greater than 1 (hazard quotient: HQ > 1), corresponding with other areas where fluoride-containing streams were traversed.…”
Section: Introductionmentioning
confidence: 99%
“…6 to 104.2 μg/L[50]. Te result was satisfed because it is in range (150-249 μg/L) of adequate the iodine intake based on the World Health Organization (WHO)/United Nations International Children's Emergency Fund (UNICEF)/International Council for Control of Iodine Defciency Disorders (ICCIDD) recommended the following epidemiological criteria[51].…”
mentioning
confidence: 99%